Absorption of soil-applied carbofuran by black pepper (Piper nigrum L.) plants in laterite soil - Wahid, Betty Bastin, P A (Journal of Spices and Aromatic Crops, 2004)
The effect of organic matter on availability of soil-applied carbofuran and its absorption by black pepper (Piper nigrum) plants were studied in a pot culture experiment employing 14C_labelled carbofuran. Absorption of carbofuran from soil was inversely related to the organic matter content of the soil. This was attributed to the enhanced degradation of the insecticide with increasing soil organic matter resulting in its reduced availability, rather than its adsorption in the soil. The absorbed carbofuran was mainly translocated to the leaf (64.0%) and stem (33.5%) and to a lesser extent to the berries (1.5%). The results also indicated that carbofuran had no phytotonic effect on black pepper plants but retarded root production.